External users in an academic libraries: a case study of Kenneth Dike Library (KDL) (2014)
Though the academic library’s primary mission is to serve the students, faculty and staff of its parent institution, would-be users not officially associated with the institution frequently call upon the library to provide services and/or resources. This paper attempts to examine the use of KDL resources/service by unaffiliated users, focusing on the user’s affiliation, status, subject areas and geographical distribution of the users with policy statement regarding the users. For this purpose, 352 user transaction request forms during the academic year 2012 were analyzed, out of which 243 (69 percent) are undergraduates, while 21(5.9 percent) are at PhD students. Users from the University community constitute 74.4 percent of external visitors to the library. The study revealed that Kenneth Dike Library supports the community use of its resources by granting access to unaffiliated users. The study therefore recommends among other things, that, access privileges must not interfere with the library’s service to its primary clientele of students, faculty and staff. Information concerning the library, particularly library use policy should be easily accessible to users who are not familiar with the library, and should be placed in strategic locations that are visible to users.